Studi Efektivitas Vaksin Influenza: Updated Review - Abednego Kristande Gwiharto; Cecep Suhandi; Cheryl Alodya; Rano K. Sinurya (KELUWIH: Jurnal Kesehatan dan Kedokteran, 2021)
Abstract—Influenza is caused by a rapidly mutating virus that consists of 2 types, namely, type A with the H1N1 and H3N2 genotypes and type B. Influenza caused global mortality with 250,000-500,000 death in 2009. The effectiveness of vaccines also changes regarding the mutation of influenza viruses, however, the development and utilization of influenza vaccines should be supported by the economic status of a country. Up to now, many countries have not prioritized the utilization of influenza vaccines. The target of influenza vaccination in children and adults (> 60 years old). The purpose of this review was to determine the effectiveness of influenza vaccines from various countries and categorize them based on their income. This review used Medline, Elsevier, and BMC Public Health as the database with the keywords "Effectiveness" and "Influenza vaccine". Then, the articles are selected based on inclusion and exclusion criteria. Based on the initial search 784 articles match the keywords, and only 13 articles met the criteria. These articles are classified based on the center of the study to classify based on their national income; 5 studies in high-income countries, 5 studies in upper-middle-income countries, 3 studies in lower-middle-income countries, and 1 study in low-income countries. The results showed that the administration of influenza vaccine in high-income and upper-middle-income countries is quite effective for type A H1N1 genotypes, whereas H3N2 is less effective. In the lower-middle-income countries, the utilization of vaccines with type A H3N2 genotype was effective, however, in the low-income countries, the effectiveness of vaccines has not been justified due to the limited study of the type of influenza and the administration of influenza vaccines in those countries. Keywords: effectiveness, high-income countries, influenza vaccine, low-income countries, middle-income countries Abstrak—Influenza disebabkan virus yang cepat bermutasi yang terdiri atas 2 tipe, yaitu tipe A dengan genotip H1N1 dan H3N2 dan tipe B. Influenza menjadi penyebab kematian 250.00 – 500.000 dari populasi dunia pada tahun 2009. Keefektivan vaksin juga berubah dengan bermutasinya virus influenza namun dalam perkembangan vaksin dan penggunaan vaksin harus didukung oleh kondisi ekonomi suatu negara. Sampai saat ini banyak negara yang belum memprioritaskan penggunaan vaksin influenza. Target vaksin influenza merupakan anak – anak dan dewasa dengan umur >60 tahun. Tujuan dari review ini adalah mengetahui keefektivan vaksin influenza dari berbagai negara berdasarkan pendapatannya. Artikel review ini menggunakan database dari Medline, Elsevier, dan BMC Public Health dengan kata kunci “Effectiveness” dan “Influenza vaccine”. Artikel yang diperoleh kemudian diseleksi berdasarkan kriteria inklusi dan eksklusi. Berdasarkan hasil penelusuran diperoleh sebanyak 784 artikel yang sesuai dengan kata kunci, kemudian artikel diseleksi kembali sehingga diperoleh 13 artikel yang masuk ke dalam kriteria review. Selanjutnya artikel tersebut diklasifikasikan berdasarkan lokasi studi sehingga diperoleh 5 studi pada negara high income, 5 studi pada negara upper-middle income, 3 studi pada negara lower-middle income, dan 1 studi pada negara low income. Hasil telaah menunjukkan bahwa pemberian vaksin influenza di negara dengan High income dan upper-middle income dinilai efektif untuk tipe A genotip H1N1, sedangkan untuk genotip H3N2 kurang efektif. Di negara lower-middle income, penggunaan vaksin pada tipe A genotip H3N2 sudah efektif, namun pada negara dengan low income belum dapat dinyatakan keefektivan dikarenakan belum terdapat hasil penelitian terkait tipe influenza dan penggunaan vaksin influenza di negara tersebut. Kata kunci: efektivitas, high-income countries, low-income countries, middle-income countries, vaksin influenza